Pedagogical knowledge in English language teaching: A lifelong-learning, complex-system perspective (UCL Press, 2020)
Pedagogical knowledge has been the subject of theoretical and empirical studies. However, no research has so far integrated the existing scholarship with data to develop and validate a framework for pedagogical knowledge in English language teaching informed by lifelong-learning, complex-system perspectives. In the absence of such research, we used a mixed method research design through a systematic review of the literature, semi-structured interviews with experienced teachers (N=10) and teacher educators (N=10), as well as a survey of 336 practising teachers in Iran to: (1) develop a framework for pedagogical knowledge; and (2) validate this framework by designing a self-assessment questionnaire for pedagogical knowledge. Our analyses yielded a nine-component model that included: knowledge of subject matter; knowledge of teaching; knowledge of students; knowledge of classroom management; knowledge of educational context; knowledge of democracy, equity and diversity; knowledge of tests/exams; knowledge of learning; and knowledge of (professional) self. Within this nine-factor framework, each component of pedagogical knowledge consists of a number of subcomponents. The proposed framework highlights the multidimensionality and complexity of pedagogical knowledge, and the mutually constitutive relationships among different knowledge domains.